Bone healing in surgically created defects treated with either bioactive glass particles, a calcium sulfate barrier, or a combination of both materials: A histological and histometric study in rat tibias - Melo, Luiz G. N. [UNESP]; Nagata, Maria José Hitomi [UNESP]; Bosco, Álvaro Francisco [UNESP]; Ribeiro, Luciana L. G. [UNESP]; Leite, Cristiane M. [UNESP] (Wiley, 2005)
Objective: The purpose of this study was to histologically analyze the influence of bioactive glass and/or a calcium sulfate barrier on bone healing in surgically created defects in rat tibias. Material and methods: Sixty-four rats were divided into 4 groups: C (control), CS (calcium sulfate), BG (bioactive glass), and BG/CS (bioactive glass/calcium sulfate). A surgical defect was created in the tibia of each animal. In Group CS, a calcium sulfate barrier was placed to cover the defect. In Group BG the defect was filled with bioactive glass. In Group BG/CS, it was filled with bioactive glass and protected by a barrier of calcium sulfate. Animals were sacrificed at 10 or 30 days post-operative. The formation of new bone in the cortical area of the defect was evaluated histomorphometrically. Results: At 10 days post-operative, Group C presented significantly more bone formation than Groups CS, BG, or BG/CS. No statistically significant differences were found between the experimental groups. At 30 days post-operative, Group C demonstrated significantly more bone formation than the experimental groups. Groups CS and BG/CS showed significantly more bone formation than Group BG. No statistically significant differences were found between Group CS and BG/CS. Conclusions: (a) the control groups had significantly more bone formation than the experimental groups; (b) at 10 days post-operative, no significant differences were found between any of the experimental groups; and (c) at 30 days post-operative, the groups with a calcium sulfate barrier had significantly more bone formation than the group that used bioactive glass only. Copyright © Blackwell Munksgaard 2005.
Keywords: Bioactive; Bone regeneration; Bone substitutes; Calcium sulfate; Glass; bioglass; calcium sulfate; animal; artificial membrane; bone prosthesis; bone regeneration; ceramics; comparative study; drug effect; image processing; male; methodology; periodontics; physiology; rat; tibia; Animals; Bone Regeneration; Bone Substitutes; Calcium Sulfate; Ceramics; Guided Tissue Regeneration, Periodontal; Image Processing, Computer-Assisted; Male; Membranes, Artificial; Rats; Tibia